Role Of Government In Agribusiness Information Systems Of Ornamental Fish Agribusiness For Increasing Income Of Fisherman Communities - Natsir, Andi Baso Adil; Ilham, Ilham (Cita konsultindo, 2023)
The City of Kediri is one of the leading exporters of commodities. The largest Betta fish producing area is in the Pesantren District, Kediri City. The role of the regional and central government is given as an effort to develop the betta fish business. This study aims to analyze the role of the government in developing the betta fish business in Kediri City with qualitative methods. One of the efforts made by the local government of the city of Kediri is to designate the Ketami village as the Harmoni Betta Village. Meanwhile, the central government has designated Kediri City as an aquaculture village. The government's role is in the form of activities and the provision of infrastructure for betta fish cultivators. Synergy is needed between programs from each agency so that the betta fish business development can run optimally.